Expression of mu-Opioid Receptor in CA1 Hippocampal Astrocytes - Nam, Min-Ho; Han, Kyung-Seok; Lee, Jaekwang; Bae, Jin Young; An, Heeyoung; Park, Seahyung; Oh, Soo-Jin; Kim, Eunju; Hwang, Eunmi; Bae, Yong Chul; Lee, C. Justin (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2018)
mu-opioid receptor (MOR) is a class of opioid receptors with a high affinity for enkephalins and beta-endorphin. In hippocampus, activation of MOR is known to enhance the neuronal excitability of pyramidal neurons, which has been mainly attributed to a disinhibition of pyramidal neurons via activating Gai subunit to suppress the presynaptic release of GABA in hippocampal interneurons. In contrast, the potential role of MOR in hippocampal astrocytes, the most abundant cell type in the brain, has remained unexplored. Here, we determine the cellular and subcellular distribution of MOR in different cell types of the hippocampus by utilizing MORm-Cherry mice and two different antibodies against MOR. Consistent with previous findings, we demonstrate that MOR expression in the CA1 pyramidal layer is co-localized with axon terminals from GABAergic inhibitory neurons but not with soma of pyramidal neurons. More importantly, we demonstrate that MOR is highly expressed in CA1 hippocampal astrocytes. The ultrastructural analysis further demonstrates that the astrocytic MOR is localized in soma and processes, but not in microdomains near synapses. Lastly, we demonstrate that astrocytes in ventral tegmental area and nucleus accumbens also express MOR. Our results provide the unprecedented evidence for the presence of MOR in astrocytes, implicating potential roles of astrocytic MOR in addictive behaviors.
Keywords: GABAERGIC NEURONS; RAT HIPPOCAMPUS; INTERNEURONS; ACTIVATION; TOLERANCE; MORPHINE; BRAIN; DELTA; AREA